The Effect of Different Energy Level on The Ration to The Mating Acceleration of Local Sheep - L Khotijah; A Maulidina; K B Satoto; I K G Wiryawan (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2018)
The aim of this research was to find the appropriate ration energy levels to determine the puberty time of ewes. The study used 12 offspring female sheep obtained from crossing Jonggol ewes of Animal Science Teaching and Research Unit (JASTRU) Faculty of Animal Science IPB with Garut male sheep. The animal age was approximately 2-3 months with the average body weight 9.79 ± 1.97 kg. The treatments were consisted of 3 rations which have different TDN level, namely: T1= 65% TDN, T2=70% TDN and T3= 75% TDN. The experimental design used was a completely randomized design with three treatments and four replications. The measured parameters were feed intake, average daily gain, and the first matting age and body weight. The data obtained were analyzed using Analysis of Variance. The results indicated that the ration energy levels did not significantly affected on the feed intake, average daily gain, as well as the first mating age and body weight. The age of first mating was 180-203 days with body weight at 18-22 kg. It is concluded that the TDN level between 65% -75% has similar response to accelerate the mating of local sheep. Keywords: energy, local sheep, mating acceleration